ANALYSIS OF EPIDEMIOLOGICAL INDICATORS OF TYPE 1 DIABETES ACCORDING TO THE REGISTER OF TOMSK AND TOMSK REGION - Yu. G. Samoilova; M. V. Novosyolova; O. A. Oleynik (Бюллетень сибирской медицины)
Type 1 diabetes mellitus (T1DM) is a serious medical and social problem in the whole world. Despite the presence of a large amount of accumulated knowledge to control the disease, there are methodological limitations and uncertainties of the register. In order to obtain complete information on the prevalence and incidence of T1DM among children and adolescents in order to monitor the disease, providing diagnostic and rehabilitation measures, there was a need for analysis of epidemiological climate T1DM in children and adolescents of the Tomsk region. The evaluation found that T1DM on the rise, especially among young children, which raises the need for а personalized approach in addressing this issue.